ENHANCING MARKETING OF FARIZ HOTEL THROUGH COORPERATING WITH GLOBAL TRAVEL AGENT - Anrico Jusuf Setiadi; Salsabila Salsabila; Yusak Adheo Widyarta; Thet Htar Zin (International Journal of Applied Business and International Management, 2018)
According to Explore Wisata (2017) Malang is a city that has many tourist destinations. Most of them located in area of Batu, there are many interesting tourist destinations. This is balanced by the number of hotels ranging from budget hotels to high star hotels that are spread around Batu. Fariz hotel is one of the hotels that compete in the budget class hotel that is surrounded by Batu area. Although Fariz hotel is a budget hotel, Fariz hotel has the better quality and service compared to the other budget hotels. Author gives an idea to make Fariz hotel entering international market. The author planned business to business co-operation to bring Fariz hotel to international. By cooperating with foreign travel agents who have package tours to Indonesia, Fariz Hotels can be added in the hotel list for the travel agent. The author chose to cooperate with foreign travel agents because the foreign tourists who will traveling usually entrusted the choice of hotel to travel agents. By entering the list of hotels in Fariz travel agent hotel will be more easily visited by foreign tourists. After cooperating with foreign travel agent, Fariz hotel will determine the right price for hotel package, hotel package price for foreign guests is certainly more expensive compared to domestic visitors, but with a slightly higher price than domestic price. With this price foreign guests will have a better service that equivalent to international budged hotel.